IMPLEMENTATION OF STORYTELLING METHOD TO IMPROVE EARLY CHILDHOOD LANGUAGE SKILLS AT KB. AL-FATH 1 - Lulu Aulia Fadhillah; Rika Purnamasari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lampung, 2025)
, The purpose of this study is to explore how storytelling can support the development of language skills in early childhood at KB Al-Fath 1. This theme was chosen because language skills are essential for cognitive, socio-emotional development, and children's readiness for formal education. A descriptive qualitative method was used for data collection in this study; observations and interviews were conducted during storytelling activities, and interviews explored the teachers' approaches to implementing this method. The study's results indicate that regularly and interactively using storytelling methods with media such as storybooks, finger puppets, and illustrated images can enrich children's vocabulary, improve their speaking skills, and boost their confidence. Additionally, this method helps children better understand basic language concepts. Despite challenges such as shy or less enthusiastic children, teachers successfully addressed them with emotional support and creative approaches. The study concludes that the storytelling method is effective not only in enhancing language skills but also in supporting the socio-emotional development of early childhood. These findings are significant as they demonstrate that storytelling can be a relevant strategy aligned with national educational standards for early childhood education